SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS PADA PENDAPATAN JASA RAWAT INAP PADA RUMAH SAKIT UMUM DAERAH: (Studi Kasus RS. Awet Muda Narmada) - Syarifah Massuki Fitri; Suandi, Suandi; Saepul Pahmi (BADAN PENERBIT STIEPARI PRESS, 2021)
This study aims to determine the accounting information system for cash receipts for inpatient service income at the regional general hospital at Narmada Awet Muda Hospital, West Lombok Regency. This type of research is descriptive qualitative. Processed data is data obtained from unstructured interviews and observations that will be analyzed qualitatively and described in descriptive form. Based on the results of the study, the accounting system for cash receipts for inpatient installations at the regional general hospital at Narmada Awet Muda Hospital is very good. This can be seen from the existence of patient admission procedures starting from inpatient registration until the patient is discharged. Likewise with cash receipts procedures that are in accordance with the existing system, namely the separation of operational functions and revenue functions as well as recording and reporting functions with supporting documents. However, the cash receipt system for inpatient installations still has several weaknesses, namely in the registration section which still needs to improve services to patients, the flow/procedure for patient payments is unclear, so it is necessary to make data flow diagrams or flowcharts in order to facilitate users of accounting information.